Familial Multiple Myeloma: Report on Two Families and Discussion of Screening Options - Gerkes Erica H; de Jong Mirjam M; Sijmons Rolf H; Vellenga Edo (Hereditary Cancer in Clinical Practice, 2007)
Abstract Multiple myeloma (MM) is a relatively rare haematological malignancy seen in older persons. It has an unknown aetiology and usually occurs incidentally within a family. However, several families have been reported with multiple cases of MM, so that the existence of hereditary MM has been postulated although no causative germline mutations have been detected so far. First-degree relatives of MM patients have been reported to have a relative risk between two and four times higher than normal of developing MM and we presume the risks are higher for relatives in the case of familial MM. Here we report on two families with MM who requested presymptomatic screening of healthy relatives. Although risk estimates for asymptomatic relatives in these types of families are not available, a clinically significant risk of developing MM cannot be excluded. We suggest that, in a research setting, screening for MM could be offered to individuals with more than one first-degree affected relative, or to those with one first-degree and at least one second-degree relative with MM. We propose a screening programme of annual protein electrophoresis of blood and urine, starting at age 40 (or earlier if a family member presented with MM at a younger age).